The Influence of Service Quaity Dimensions on Outatient Patient Satisfaction i During the Covid 19: The Influence of Service Quality Dimensions on Outpatient Patient Satisfaction During the Covid 19 Pandemic at the Tanah Laut Public Health Center - Maulana Setiyo Budi; Ibrahim Daud; Zainal Arifin (Health Media, 2022)
This study aims to analyze the effect of the tangible, reliability, responsiveness, assurance, and empathy dimensions simultaneously on outpatient satisfaction during the Covid-19 pandemic. This type of research is explanatory research which explains the position of the variables studied in a study. The research sample was 100 patients receiving outpatient treatment taken at random during the pandemic in the village of Penyipatan, Tanah Laut Regency The results of the study show that the dimensions of tangible, reliability, assurance, and empathy significantly affect outpatient satisfaction during the Covid-19 pandemic, while responsiveness has no significant effect. This shows that the level of public fear during the great Covid -19 pandemic made the demands for their service care very high beyond the response ability of health workers.